Defective carbon electrocatalysts and methods of making the same
Patent Information
- Application Number
- CN202310570609.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-16
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-05-16
AI Technical Summary
[0028]与现有技术相比,本发明的有益效果在于:通过本发明的缺陷碳电催化剂及电催化剂的制备方法,与传统的电催化剂相比,由于曲率效应,因此可提高活性和耐久性。本发明的电催化剂载体可适用于燃料电池的氧还原反应(Oxygen Reduction Reaction,ORR)。
Smart Images

Figure CN116435531B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy, specifically to defective carbon electrocatalysts, their preparation methods, and their application in the oxygen reduction reaction of fuel cells. Background Technology
[0002] With the increasing depletion of fossil fuels, the development of clean energy is crucial for the sustainable and green development of human society. As one of the most important technologies for developing clean new energy sources, electrocatalysis is vital for global development. Current cutting-edge international research focuses on the design and development of high-performance electrocatalysts.
[0003] Generally, well-designed electrocatalysts should exhibit optimized physical or chemical properties to facilitate adsorption and desorption processes and achieve good performance. Therefore, controlling the arrangement of atoms on the catalyst surface plays a crucial role in electrocatalysis. By adjusting the structure and morphology of the electrocatalyst, the formation of catalytic reaction intermediates and the release of final products can be modulated. Furthermore, activity can be improved by increasing the utilization of active sites, such as through high-load single-atom strategies. Mass transfer during the reaction process accelerates the efficiency of the electrocatalyst by improving the kinetics of the electrocatalytic reaction, such as by adjusting the catalyst's pore size and particle size. Finally, enhancing the intrinsic activity of the electrocatalyst is also an effective way to optimize its catalytic performance. These strategies rationally control the relationship between catalyst structure and its electrocatalytic performance, promoting the development and design of novel electrocatalysts.
[0004] Density functional theory (DFT) calculations and molecular dynamics (MD) simulations have confirmed that rough surfaces in catalysts lead to non-uniform charge distribution and promote strain and electric field effects. These results indicate that the adsorption and desorption of reactants, intermediates, and products during electrocatalysis can be altered by adjusting the curvature of the catalytic surface. Therefore, electrocatalysts with different surface curvatures have attracted significant attention from researchers for improving electrocatalytic activity.
[0005] Our research focuses on the role of surface curvature in electrocatalysis and explores the electrocatalytic performance of defective carbon catalysts with heteroatoms modifying surface curvature, aiming to design highly efficient electrocatalysts to promote the development of clean energy. Summary of the Invention
[0006] This invention provides a defective carbon electrocatalyst and a method for preparing the electrocatalyst, aiming to study the curvature effect of carbon defects and solve the technical problems of how to improve the activity and durability of carbon-based electrocatalysts.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a defective carbon electrocatalyst, which is prepared by the following method:
[0009] (1) Sodium tellurite and polyvinylpyrrolidone are dissolved in water A, and ammonia solution and hydrazine hydrate solution are added. After uniform dispersion, the mixture is reacted at 175-185℃ for 170-190 min (preferably 180℃ for 180 min). The resulting reaction solution A is post-treated A to obtain Te nanowires. The mass ratio of ammonium hydroxide in sodium tellurite, polyvinylpyrrolidone, and ammonia solution to hydrazine hydrate in hydrazine hydrate solution is 0.09:0.99-1.04:0.745-0.767:1.23-1.31 (preferably 0.09:1:0.756:1.272).
[0010] (2) The Te nanowires, hexamethylenetetramine, and phenol described in step (1) are uniformly dispersed in water B and reacted at 155-165℃ for 230-250 min (preferably 160℃ for 240 min). The resulting reaction solution B is then post-treated to obtain Te@PFR. The molar ratio of the hexamethylenetetramine, phenol, and sodium tellurite described in step (1) is 0.000998-0.00285:0.0004-0.0015:0.000077 (preferably 0.0025:0.001:0.000077).
[0011] (3) Place the Te@PFR obtained in step (2) together with melamine under a protective atmosphere and calcine at 650-750℃ for 100-140 min (preferably 700℃, 120 min) and then calcine at 1100-1150℃ for 100-120 min (preferably 1150℃, 120 min) to obtain the defective carbon electrocatalyst; the mass ratio of Te@PFR to melamine is 1:1-3 (preferably 1:1). Te@PFR and melamine should not be mixed. The amount of melamine should not be too small, as it is related to the number of defects. Too little melamine will lead to a reduction in active sites and thus poor performance.
[0012] Furthermore, the volume of water A in step (1) is 376.48-407.89 mL / g (preferably 391.11 mL / g) based on the mass of sodium tellurite.
[0013] Furthermore, the concentration of the ammonia solution in step (1) is 20-30 wt%, and in one embodiment of the present invention it is 25 wt%. The concentration of the hydrated hydrazine solution is 80-85 wt%, and in one embodiment of the present invention it is 85 wt%.
[0014] In one embodiment of the present invention, the post-processing A in step (1) is as follows: the reaction solution A is naturally cooled to room temperature, centrifuged, and the resulting precipitate is washed with acetone by centrifugation to obtain Te nanowires.
[0015] Furthermore, the volume of water B in step (2) is 2035.09-2058.48 mL / g (preferably 2046.78 mL / g) based on the mass of sodium tellurite in step (1).
[0016] In one embodiment of the present invention, the phenol is added in the form of an aqueous solution of phenol, and the concentration of the aqueous solution of phenol is 0.1M.
[0017] In one embodiment of the present invention, the post-processing B in step (2) is as follows: the obtained reaction solution B is cooled to room temperature, filtered, the obtained filter cake is washed with deionized water, dried, and the Te@PFR is obtained.
[0018] Furthermore, the protective atmosphere described in step (3) is nitrogen, or it can be an inert gas, such as argon.
[0019] The letters mentioned above are only used to distinguish materials and operations at different stages and have no other special meaning.
[0020] The quasi-metallic element powder is dissolved to obtain a mixture; the obtained mixture is used to synthesize phenolic resin-coated quasi-metallic element nanowires; the phenolic resin-coated quasi-metallic element nanowires are heat-treated under an inert atmosphere to obtain an electrocatalyst, in which the quasi-metallic element evaporates after high-temperature pyrolysis.
[0021] Optionally, the step of dissolving the metalloid powder to obtain a mixture includes: adding the metalloid powder and polyvinylpyrrolidone to deionized water and stirring; sequentially adding analytical grade ammonia solution and hydrated hydrazine and stirring, wherein the total time required for stirring is half an hour.
[0022] Optionally, the step of synthesizing the obtained mixture into phenolic resin-coated quasi-metallic nanowires and carbonizing them includes: centrifuging the mixture to precipitate, adding it to deionized water with hexamethylenetetramine and phenol solutions and stirring to obtain a mixed solution; heating to 160 degrees Celsius and continuing to heat for 240 minutes; cooling the product after reaction to room temperature; washing and filtering the product after reaction with deionized water and drying it; placing the dried product and melamine (mass ratio 1:1) in a quartz boat and calcining it at 700 degrees Celsius for 2 hours, then continuing to heat it to 1150 degrees Celsius and holding it at that temperature for 2 hours, and then cooling it to room temperature to obtain a defect carbon catalyst.
[0023] The obtained electrocatalyst is mainly composed of carbon, and also contains trace amounts of nitrogen and oxygen.
[0024] The obtained electrocatalyst is a nanowire structure with a length in the micrometer range and a diameter in the range of 100 to 200 nanometers.
[0025] The specific surface area of the obtained electrocatalyst is greater than or equal to 227 square meters per gram.
[0026] Phenolic resin-coated quasi-metal nanowires and carbonization were synthesized using a reaction vessel.
[0027] Secondly, the present invention also provides the application of the above-mentioned defective carbon electrocatalyst in the catalytic oxygen reduction reaction.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: Due to the curvature effect, the defective carbon electrocatalyst and its preparation method of the present invention can improve the activity and durability of conventional electrocatalysts. The electrocatalyst support of the present invention is applicable to the oxygen reduction reaction (ORR) in fuel cells. Attached Figure Description
[0029] Figure 1 This is a flowchart of the preparation method of an exemplary embodiment of the present invention.
[0030] Figure 2 This is a schematic diagram of the surface morphology of the LCDC according to an exemplary embodiment 1 of the present invention.
[0031] Figure 3 This is a schematic diagram of the surface morphology of HCDC in an exemplary embodiment 2 of the present invention.
[0032] Figure 4 These are Raman diagrams of exemplary embodiments 1 and 2 of the present invention.
[0033] Figure 5 This is a schematic diagram of the LSV test results of exemplary embodiments 1-3 of the present invention.
[0034] Figure 6 This is a schematic diagram of the LSV test results of exemplary embodiments 1 and 4 of the present invention.
[0035] Figure 7 This is a schematic diagram of the LSV test results of exemplary embodiments 2 and 5 of the present invention.
[0036] Figure 8 This is a schematic diagram of the durability current value change in exemplary embodiment 2 of the present invention.
[0037] Figure 9 This is a schematic diagram of the LSV test results of exemplary embodiment 6 of the present invention.
[0038] Figure 10 This is a schematic diagram of the LSV test results of exemplary embodiment 7 of the present invention.
[0039] Figure 11 This is a schematic diagram of the LSV test results of exemplary embodiment 8 of the present invention. Detailed Implementation
[0040] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0041] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0042] The electrocatalyst can be used in fuel cells. The curvature effect in the carbon-based electrocatalyst of the present invention, for example, shows better reaction kinetics and durability on curved surfaces compared to planar defect carbon electrocatalysts. Additionally, in the exemplary embodiment, the temperature is in degrees Celsius.
[0043] Reference Figure 1 The preparation method shown, an exemplary embodiment of the electrocatalyst preparation method includes: dissolving a quasi-metallic element powder to obtain a mixture; synthesizing the obtained mixture into phenolic resin-coated quasi-metallic nanowires; and heat-treating a precursor doped with N under an inert atmosphere to obtain the electrocatalyst, wherein the dissolved substances corresponding to each 0.09 g of quasi-metallic element powder include: 1 g of polyvinylpyrrolidone, 35.2 mL of deionized water, 0.756 g of ammonium hydroxide, and 1.272 g of hydrazine hydrate, wherein the quasi-metallic element in the obtained electrocatalyst evaporates after high-temperature heat treatment. As an example, the step of dissolving the quasi-metallic element powder to obtain the mixture includes: adding the quasi-metallic element powder and polyvinylpyrrolidone to deionized water and stirring; sequentially adding analytical grade ammonia solution and hydrazine hydrate while stirring, wherein the total stirring time is 0.5 hours.
[0044] As an example, the steps for synthesizing phenolic resin-coated quasi-metallic element nanowires and carbonization of the obtained mixture include: centrifuging the mixture to precipitate, adding it to deionized water with hexamethylenetetramine and phenol solution and stirring to obtain a mixed solution; heating to 160 degrees Celsius and continuing heating for 240 minutes; cooling the product after reaction to room temperature; washing and filtering the product after reaction with deionized water and drying it; placing the dried product and melamine (1:1) in a quartz boat and calcining it at 700 degrees Celsius for 2 hours, then continuing to heat to 1150 degrees Celsius and holding it at that temperature for 2 hours, and then cooling it to room temperature to obtain a carbon-based catalyst.
[0045] As an example, tellurium is a near-metallic element.
[0046] As an example, the main element in an electrocatalyst is carbon, and it also contains trace amounts of nitrogen and oxygen.
[0047] As an example, the obtained electrocatalyst is a nanowire structure with a length in the micrometer range and a diameter in the range of 100 to 200 nanometers.
[0048] As an example, the specific surface area of the obtained electrocatalyst support is greater than or equal to 227 square meters per gram.
[0049] As an example, the near-metallic element powder is dissolved at room temperature, and / or the concentration of the analytical grade ammonia solution is 25%, and / or the concentration of the analytical grade aqueous hydrazine solution is 85%. The volume ratio of the analytical grade ammonia solution to the analytical grade hydrogen peroxide solution is 29:67.
[0050] As an example, phenolic resin-coated quasi-metal nanowires are synthesized in a reactor with a filling rate of 20% to 35%, and / or the gas used for heat treatment in an inert atmosphere contains nitrogen, and / or the mass ratio of precursor to melamine is 1:1, and / or the temperature used for heat treatment in an inert atmosphere is 700°C to 1150°C, and / or the duration of heat treatment in an inert atmosphere is 0.5 hours to 4 hours.
[0051] An exemplary embodiment, in another aspect, provides a defective carbon electrocatalyst. The electrocatalyst is prepared via a defective carbon electrocatalyst preparation method of an exemplary embodiment.
[0052] Example 1
[0053] This exemplary embodiment describes the preparation of LCDC. Sodium tellurite and polyvinylpyrrolidone can be dissolved in deionized water, followed by reduction with hydrazine hydrate and ammonia to prepare a mixture. Te@PFR NFs can then be prepared via hydrothermal treatment. The N-doped carbon material is subjected to heat treatment at 700°C and 1150°C to obtain LCDC, i.e., the electrocatalyst.
[0054] The preparation process is as follows: 0.09 g (0.000406 mol) of sodium tellurite and 1 g of polyvinylpyrrolidone were added to 35.2 mL of deionized water and stirred slowly under good ventilation and at room temperature. Then, 3.35 mL of analytical grade ammonia solution (25% w / w, 0.756 g ammonium hydroxide) and 1.45 mL of hydrazine hydrate (85% w / w, 1.272 g hydrazine hydrate) were added dropwise sequentially to the solution, and the mixture was stirred slowly for half an hour. The solution was then transferred to a polytetrafluoroethylene container, which was then transferred to a 50 mL reaction vessel and heated to 180°C in an oven for 180 minutes. During the reaction, the solution reacted and produced a linear substance. After the reaction was completed and the mixture was allowed to cool naturally to room temperature (e.g., 24°C), 7.6 mL of the previously prepared Te nanowire mother liquor (theoretically prepared from 0.000077 mol sodium tellurite) was taken and repeatedly centrifuged with acetone to obtain a precipitate. Then, 0.14 g of 0.0001 mol hexamethylenetetramine, 4 mL of phenol aqueous solution (0.1 mol / L, 0.0004 mol phenol), and 31 mL of deionized water were added for a hydrothermal reaction. The mixture was heated to 160°C for 240 minutes, cooled, washed with deionized water, and the organic matter was filtered off. After drying, a certain amount of the dried Te@PFR NFs was mixed with melamine (1:1) and placed in a quartz boat. The mixture was calcined under nitrogen at 700°C for 2 hours and then at 1150°C for 2 hours. After cooling, the LCDC catalyst was obtained.
[0055] Surface morphology analysis is as follows: The surface morphology of LCDC obtained after heat treatment in an inert atmosphere was observed using a scanning electron microscope (SEM). The results are as follows. Figure 2 As shown, the prepared LCDC exhibits a nanowire structure.
[0056] Raman analysis is as follows: The D and G bands of LCDC were analyzed using Raman spectroscopy, and the results are as follows. Figure 4 As shown. After heat treatment, ID / IG is approximately 0.975. Figure 5 For LSV testing, a three-electrode DC testing method was used. The powder sample was placed on a rotating disk electrode, and the half-wave potential of LCDC was measured to be 0.724V.
[0057] Example 2
[0058] This exemplary embodiment prepares HCDC. Sodium tellurite and polyvinylpyrrolidone can be dissolved in deionized water, followed by reduction with hydrazine hydrate and ammonia to prepare a mixture. Te@PFR NNs can then be prepared via hydrothermal treatment. The N-doped carbon material is subjected to inert atmosphere heat treatment at 700°C and 1150°C to obtain HCDC, i.e., the electrocatalyst.
[0059] The preparation process is as follows: 0.09 g (0.000406 mol) of sodium tellurite and 1 g of polyvinylpyrrolidone were added to 35.2 mL of deionized water and stirred slowly under good ventilation and at room temperature. Then, 3.35 mL of analytical grade ammonia solution (25% w / w, 0.756 g ammonium hydroxide) and 1.45 mL of hydrazine hydrate (85% w / w, 1.272 g hydrazine hydrate) were added dropwise sequentially to the solution, and the mixture was stirred slowly for half an hour. The solution was then transferred to a polytetrafluoroethylene container, which was then transferred to a 50 mL reaction vessel and heated to 180°C in an oven for 180 minutes. During the reaction, the solution reacted and produced a linear substance. After the reaction was completed and the mixture was allowed to cool naturally to room temperature (e.g., 24°C), 7.6 mL of the previously prepared Te nanowire mother liquor (theoretically prepared from 0.000077 mol sodium tellurite) was taken and repeatedly centrifuged with acetone to obtain a precipitate. Then, 0.35 g of 0.0025 mol hexamethylenetetramine, 10 mL of phenol solution (0.1 mol / L, 0.001 mol phenol), and 25 mL of deionized water were added for a hydrothermal reaction. The mixture was heated to 160°C for 240 minutes. After cooling, the mixture was washed with deionized water and the organic matter was filtered off. After drying, a certain amount of the dried Te@PFR NNs was mixed with melamine (1:1) and placed in a quartz boat. The mixture was then calcined in nitrogen at 700°C for 2 hours and then at 1150°C for 2 hours. After cooling, the HCDC catalyst was obtained.
[0060] Surface morphology analysis is as follows: The surface morphology of LCDC obtained after heat treatment in an inert atmosphere was observed using a scanning electron microscope (SEM). The results are as follows. Figure 2 As shown, the prepared HCDC exhibits a nanonecklace-like structure.
[0061] Raman analysis is as follows: The D and G bands of HCDC were analyzed using Raman spectroscopy, and the results are as follows. Figure 4 As shown. After heat treatment, ID / IG is approximately 0.996. Figure 5 For LSV testing, a three-electrode DC testing method was used. The powder sample was placed on a rotating disk electrode, and the electrocatalytic activity of the material was found to be optimal, with the most positive half-wave potential being 0.842V.
[0062] The electrochemical durability test is as follows: Figure 8 The electrochemical durability test results for HCDC were obtained by uniformly coating 12 μL of catalyst (5 mg / mL) onto a rotating ring-disc electrode, with a mass loading density of 0.6 mg / cm² for all samples. Furthermore, the measured potential was converted to a reversible hydrogen electrode (RHE) using the following formula: E (relative heat exchange coefficient) = E (silver / silver chloride) + 0.059pH + 0.197. Figure 8 The electrochemical stability was evaluated using a constant current electrocatalysis method. The performance remained almost unchanged (92.7%) after 12 hours.
[0063] Example 3
[0064] The experimental procedure of Example 3 was repeated in Example 1, except for the amount of materials used: "0.28 g of hexamethylenetetramine, 0.002 mol, 8 mL of phenol solution (0.1 mol / L) (0.0008 mol phenol) and 27 mL of deionized water were required". Other conditions and procedures were the same as in Example 1, and the MCDC catalyst was finally obtained.
[0065] Figure 5 For LSV testing, a three-electrode DC testing method was used. The powder sample was placed on a rotating disk electrode, and the half-wave potential of the material was measured to be 0.808V, which is higher than LCDC and lower than HCDC.
[0066] Example 4
[0067] This exemplary embodiment describes the preparation of LCC. Sodium tellurite and polyvinylpyrrolidone (PVP) are dissolved in deionized water, followed by reduction with hydrazine hydrate and ammonia to prepare a mixture. Te@PFR NFs are then prepared via hydrothermal treatment. Finally, the mixture is subjected to heat treatment at 1150 degrees Celsius to obtain the LCC, i.e., the electrocatalyst.
[0068] The preparation process is as follows: 0.09 g (0.000406 mol) of sodium tellurite and 1 g of polyvinylpyrrolidone were added to 35.2 mL of deionized water and stirred slowly under good ventilation and at room temperature. Then, 3.35 mL of analytical grade ammonia solution (25% w / w, 0.756 g ammonium hydroxide) and 1.45 mL of hydrazine hydrate (85% w / w, 1.272 g hydrazine hydrate) were added dropwise sequentially to the solution, and the mixture was stirred slowly for half an hour. The solution was then transferred to a polytetrafluoroethylene container, which was then transferred to a 50 mL reaction vessel and heated to 180°C in an oven for 180 minutes. During the reaction, the solution reacted and produced a linear substance. After the reaction was completed and the mixture was allowed to cool naturally to room temperature (e.g., 24°C), 7.6 mL of the previously prepared Te nanowire mother liquor (0.000077 mol sodium tellurite) was taken and repeatedly centrifuged with acetone to obtain a precipitate. Then, 0.0001 mol, 0.14 g of hexamethylenetetramine, 4 mL of phenol aqueous solution (0.1 mol / L, 0.0004 mol phenol), and 31 mL of deionized water were added to initiate a hydrothermal reaction. The mixture was heated to 160°C for 240 minutes, cooled, washed with deionized water, and the organic matter was filtered off. After drying, a certain amount of the dried Te@PFR NFs was placed in a quartz boat and calcined at 1150°C for 2 hours under nitrogen. After cooling, the LCC catalyst was obtained.
[0069] Figure 6 For LSV testing, a three-electrode DC testing method was used. The powder sample was placed on a rotating disk electrode, and the half-wave potential of the LCC material was measured to be 0.67V, which is lower than that of LCDC.
[0070] Example 5
[0071] This exemplary embodiment describes the preparation of HCC. Sodium tellurite and polyvinylpyrrolidone are dissolved in deionized water, followed by reduction with hydrazine hydrate and ammonia to prepare a mixture. Te@PFR NNs are then prepared via hydrothermal treatment. Finally, HCC, i.e., the electrocatalyst, is obtained by heat treatment at 1150 degrees Celsius.
[0072] The preparation process is as follows: 0.09 g (0.000406 mol) of sodium tellurite and 1 g of polyvinylpyrrolidone were added to 35.2 mL of deionized water and stirred slowly under good ventilation and at room temperature. Then, 3.35 mL of analytical grade ammonia solution (25% w / w, 0.756 g ammonium hydroxide) and 1.45 mL of hydrazine hydrate (85% w / w, 1.272 g hydrazine hydrate) were added dropwise sequentially to the solution, and the mixture was stirred slowly for half an hour. The solution was then transferred to a polytetrafluoroethylene container, which was then transferred to a 50 mL reaction vessel and heated to 180°C in an oven for 180 minutes. During the reaction, the solution reacted and produced a linear substance. After the reaction was completed and the mixture was allowed to cool naturally to room temperature (e.g., 24°C), 7.6 mL of the previously prepared Te nanowire mother liquor (0.000077 mol sodium tellurite) was taken and repeatedly centrifuged with acetone to obtain a precipitate. Then, 0.35 g of 0.0025 mol hexamethylenetetramine, 10 mL of phenol aqueous solution (0.1 mol / L, 0.001 mol phenol), and 25 mL of deionized water were added to initiate a hydrothermal reaction. The mixture was heated to 160°C for 240 minutes, cooled, washed with deionized water, and the organic matter was filtered off. After drying, a certain amount of the dried Te@PFR NNs was placed in a quartz boat and calcined at 1150°C for 2 hours under nitrogen. After cooling, the HCC catalyst was obtained.
[0073] Figure 7 For LSV testing, a three-electrode DC testing method was used. The powder sample was placed on a rotating disk electrode, and the half-wave potential of the material was measured to be 0.781V, which is higher than LCC and lower than HCDC.
[0074] Example 6
[0075] The other operations in Example 6 are the same as in Example 2, except that the calcination process is only carried out once, under the conditions of 700 degrees Celsius for 2 hours, and finally an electrocatalyst is obtained.
[0076] Figure 9 For LSV testing, a three-electrode DC testing method was used. The powder sample was placed on a rotating disk electrode, and the half-wave potential of the material was measured to be 0.633V.
[0077] Example 7
[0078] The other operations in Example 7 are the same as in Example 1, except that the calcination process is only carried out once, under the conditions of 1150 degrees Celsius for 2 hours, and finally an electrocatalyst is obtained.
[0079] Figure 10 For LSV testing, a three-electrode DC testing method was used. The powder sample was placed on a rotating disk electrode, and the half-wave potential of the material was measured to be 0.761V.
[0080] Example 8
[0081] The other operations in Example 8 are the same as in Example 2, except that the ratio of Te@PFR NNs to melamine is 1:3, and the calcination process is the same as in Example 2, ultimately obtaining an electrocatalyst.
[0082] Figure 11 For LSV testing, a three-electrode DC testing method was used. The powder sample was placed on a rotating disk electrode, and the half-wave potential of the material was measured to be comparable to that of HCDC, with a half-wave potential of 0.841V.
[0083] The electrocatalyst nanowire structures obtained through exemplary embodiments have lengths in the micrometer range and diameters ranging from 120 to 200 nanometers. The specific surface areas of the electrocatalyst supports obtained through exemplary embodiments are 227 m² / g and 390 m² / g. The metalloid element in the exemplary embodiments is tellurium.
[0084] All of the above technical solutions can be combined in any way to form optional embodiments of the present invention, and will not be described in detail here.
[0085] Through exemplary embodiments of the present invention, a defective carbon catalyst can be obtained, wherein topological carbon defects are generated after heteroatom doping and heat treatment under an inert atmosphere. Current research progress indicates that the morphology of synthesized carbon catalysts can be controlled to improve their activity and enhance their performance and durability. Theoretical calculations show that active sites have lower energy barriers on curved surfaces. The electrocatalyst of the present invention features simplified processes and reduced costs, and the amount of heteroatom doping and the concentration of phenolic resin can be controlled as needed to adjust the curvature of the electrocatalyst. Since the prepared electrocatalyst is a carbon material, attention must be paid to the oxidation of the carbon material, for example, avoiding contact with oxygen at high temperatures. Furthermore, since the preparation environment is non-acidic, safety is improved, for example, the safety of the heat treatment required for the synthesis of HCDC.
[0086] This invention uses specific examples to illustrate the principles and implementation methods of the invention. The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the invention. Therefore, the content of this specification should not be construed as a limitation of the invention.
Claims
1. A defective carbon electrocatalyst, characterized in that... The defective carbon electrocatalyst was prepared by the following method: (1) Sodium tellurite and polyvinylpyrrolidone are dissolved in water A, and ammonia solution and hydrazine hydrate solution are added. After uniform dispersion, the mixture is reacted at 175-185℃ for 170-190 min. The resulting reaction solution A is post-treated to obtain Te nanowires. The mass ratio of ammonium hydroxide in sodium tellurite, polyvinylpyrrolidone, and ammonia solution to hydrazine hydrate in hydrazine hydrate solution is 0.09:0.99-1.04:0.745-0.767:1.23-1.
31. (2) The Te nanowires, hexamethylenetetramine, and phenol described in step (1) are uniformly dispersed in water B and reacted at 155-165℃ for 230-250 min. The resulting reaction solution B is post-treated to obtain Te@PFR. The molar ratio of the hexamethylenetetramine, phenol, and sodium tellurite described in step (1) is 0.000998-0.00285: 0.0004-0.0015: 0.000077. (3) Place the Te@PFR obtained in step (2) together with melamine under a protective atmosphere, and calcine at 650-750℃ for 100-140 min for the first time, and at 1100-1150℃ for the second time for 100-120 min to obtain the defective carbon electrocatalyst; the mass ratio of Te@PFR to melamine is 1:1-3.
2. The defective carbon electrocatalyst as described in claim 1, characterized in that: The volume of water A in step (1) is 376.48-407.89 mL / g based on the mass of sodium tellurite.
3. The defective carbon electrocatalyst as described in claim 1, characterized in that: The concentration of the ammonia solution in step (1) is 20-30 wt%, and the concentration of the hydrated hydrazine solution is 80-85 wt%.
4. The defective carbon electrocatalyst as described in claim 1, characterized in that... The post-treatment A in step (1) is as follows: the reaction solution A is naturally cooled to room temperature, centrifuged, and the resulting precipitate is washed with acetone by centrifugation to obtain Te nanowires.
5. The defective carbon electrocatalyst as described in claim 1, characterized in that: The volume of water B in step (2) is 2035.09-2058.48 mL / g, based on the mass of sodium tellurite in step (1).
6. The defective carbon electrocatalyst as described in claim 1, characterized in that: In step (2), the phenol is added in the form of an aqueous solution of phenol, and the concentration of the aqueous solution of phenol is 0.1M.
7. The defective carbon electrocatalyst as described in claim 1, characterized in that: The post-treatment B in step (2) is as follows: cool the obtained reaction solution B to room temperature, filter it, wash the obtained filter cake with deionized water, and dry it to obtain the Te@PFR.
8. The defective carbon electrocatalyst as described in claim 1, characterized in that: The mass ratio of Te@PFR to melamine is 1:1-3.
9. The defective carbon electrocatalyst as described in claim 1, characterized in that: The protective atmosphere described in step (3) is nitrogen.
10. The application of the defective carbon electrocatalyst as described in claim 1 in the catalytic oxygen reduction reaction.
Citation Information
Patent Citations
Method of operating a methanol fuel cell and a methanol fuel cell with an anode catalyst comprising tellurium
CN101589502A
Preparation method of high-strength and high-toughness silicon carbide nanowire reinforced silicon carbide ceramic composite material
CN111995418A